Peningkatan Kemampuan Degradasi ZnO Terhadap Rhodamin B Dengan Impregnasinya Pada Karbon Aktif Dari Ampas Tebu - Winda Anisa; Miftahul Khair (Jurnal Periodic Jurusan Kimia UNP, 2022)
Research has been carried out with the aim of knowing the characteristics of activated carbon made from bagasse waste to be used as a support for zinc oxide (ZnO) catalysts using the impregnation method and the ability of the catalyst to degrade Rhodamin B dyes. Activated carbon is impregnated with Zn(NO3)2.6H2O with variations activated carbon 5%, 10%, 15%, 20%, and 25% to 15 gram mass of Zn(NO3)2.6H2O. The impregnated KA/ZnO was then contacted with 10 ppm Rhodamine B dye with a degradation time of 120 minutes. The mass of KA/ZnO used was 25 mg, 50 mg and 75 mg. The FTIR (Fourier Transform Infra Red) results of the KA/ZnO catalyst show that Zn-O molecules have entered into the pores of the activated carbon marked by the appearance of absorption peaks at wavelengths of 426.28 cm-1, 419.52 cm-1, and 437.85 cm-1 . The results of UV-Vis spectrophotometer measurements obtained the highest degradation percentage of Rhodamin B dye, namely 88.23% at 10% KA/ZnO with a catalyst mass of 75 mg.